Effects of wetland, tide, and season on benthic biofilms and related sediment properties in mangrove ecosystems - Yang, Lihua; Yang, Qian; Lin, Li; Luan, Tiangang; Yang, Qiong; Li, Pu; Tam, Nora F. Y. (Frontiers in Marine Science, 2022)
Sediment biofilms, mainly composed of diatoms, bacteria, and related extracellular polymeric substances (EPS), play important roles in mangrove ecosystems. In order to better understand the microbial biodiversity in marine environment, this study aims to clarify the effects of wetland, season, and tide on benthic biofilms and related sediment properties based on in situ investigation in two mangrove wetlands (Futian and Qi’ao) in the Pearl River Estuary, South China. Owing to the tide current, the northeastern Futian is more influenced by seawater than the southwestern Qi’ao. As a consequence of the salinity-driven accumulation of nutrients in sediments, Futian is more eutrophic than Qi’ao. Compared to Qi’ao, the higher nutrimental condition in Futian conserves higher abundance of eutrophic indicators of Nitzschia and Cyclotella, which results in higher values of all pigments and bound polysaccharide with varied monosaccharide composition. Compared to the seaward site, the landward site has higher abundance of benthic (pennate) diatoms but lower abundance of planktonic (centric) diatoms due to the varied settling velocity by tidal disturbance. This varied diatom composition leads to higher levels of bound polysaccharide and more monosaccharides in the landward site than in the seaward site. Compared to late spring (March), early summer (May) appears to have similar diatom abundance but more EPS fractions (except bound protein) and monosaccharides due to the higher level of light intensity and temperature. The observed lower bacterial abundance in May than in March might be due to the higher predation pressure. The baseline data on biofilm compositions in mangrove ecosystems from this study can improve the understanding of microbial biodiversity in response to the tidal, temporal, and spatial changes.